Agricultural Law - Center for Natural Resources; Michael Olexa; Bruce Delaney (EDIS, 2003)
Creation of the Environmental Protection Agency in 1970 brought with it a number of new and amended pre-existing environmental laws designed to monitor and regulate agricultural production practices. These laws and their corresponding regulations have implemented environmental policies designed to oversee all aspects of agriculture. The agricultural industry has adapted to this regulatory atmosphere by actively involving itself within the legislative process. Because of this, the industry has a better understanding of critical environmental issues and the importance of addressing these issues through cooperation and compromise. This publication was produced by the Center for Natural Resources at the University of Florida. CNR 5 is part of a Program Summary Series. First published: September 2000. Minor revision: March 2003.